Non-criteria antiphospholipid antibodies and pediatric rheumatic disease: a case series - Shawn A. Mahmud; Danielle R. Bullock; Colleen K. Correll; Patricia M. Hobday; Mona M. Riskalla; Richard K. Vehe; Bryce A. Binstadt (BMC, 2022)
Abstract Background Non-criteria antiphospholipid antibodies (NC-aPL) are a relatively undefined subgroup of antiphospholipid antibodies (aPL). Knowledge about NC-aPL in adults is limited and even less is known in pediatric patients. Routine tests for antiphospholipid syndrome (APS)-a clinical state marked by the presence of aPL in association with vascular thrombosis-usually include lupus anticoagulant (LAC), anti-cardiolipin (aCL) and -beta-2 glycoprotein I (aβ2GPI). LAC is a functional screen for prothrombotic aPL, while the latter tests identify specific autoantibodies. Specific targets of NC-aPL include, but are not limited to, phosphatidylethanolamine, phosphatidylserine, and prothrombin. Presentation of cases We present single-center data from eight pediatric patients with NC-aPL identified during a three-year period. All patients had presenting features raising suspicion for APS. Most patients were female with a primary rheumatic disease. One patient had a stroke. Another patient had alveolar hemorrhage and pulmonary hypertension. Raynaud's phenomenon, rashes involving distal extremities, and headaches were common. Most patients had a positive LAC, yet their routine aPL tests were negative, prompting testing for NC-aPL. Conclusions Our findings suggest NC-aPL are associated with typical signs and symptoms of APS in pediatric patients. Pediatricians and pediatric subspecialists should consider NC-aPL when clinical suspicion is high and routine aPL tests are negative, particularly when LAC is positive. While guidelines for NC-aPL do not yet exist for children or adults, these autoantibodies have pathogenic potential. Actionable items could include evaluation for the presence of other (primary) rheumatic diseases, and consultation with hematologists and/or obstetricians regarding anticoagulation/platelet inhibition and thrombosis education. Future guidelines regarding NC-aPL will only be generated by gathering more data, ideally prospectively.